N 2 proportion in GIL based on heat characteristics of gas mixture - PANG Lele; YANG Wenyong; LI Pengfei; GUO Xiaofei; GAO Peng; LIANG Rui (电力工程技术, 2022)
SF 6/N 2 gas mixture is considered as one of the most promising gases to replace SF 6 because of its good insulation performance and environmental benefits. However,there is a lack of research on the mixing ratio of SF 6/N 2 gas mixture in different conditions. Under the premise of ensuring the insulation level of gas-insulated transmission lines (GIL),a multi-physical field coupling calculation model is established. From the perspective of heat characteristics of gas mixture,the relationship between SF 6/N 2 mixing ratio and GIL temperature rise under different insulating gas pressure,load current and ambient temperature is analyzed to determine the appropriate SF 6/N 2 mixture ratio under different conditions. The results show that there is a negative correlation between the insulation gas pressure (or the SF 6 content) and GIL temperature rise at the same pressure. The SF 6 content is suggested to be in the range of 40%~60% when the load current exceeds 3 kA for a long period of time,40%~70% when the equipment is running in the middle and low latitudes,and 30%~40% when the equipment is in the high latitudes. In addition,considering the safety margin,the insulation and temperature rise requirements of GIL can be met when SF 6 content is not less than 70% of the recommended value.